2017
DOI: 10.1002/pros.23465
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune‐inflammation index predicts the combined clinical outcome after sequential therapy with abiraterone and docetaxel for metastatic castration‐resistant prostate cancer patients

Abstract: In this study, we did not observe differences in clinical outcomes based on alternative sequencing of AA and DP in mCRPC patients. The ability to tolerate side effects and patient preference may be used to determine the treatment sequencing. In addition, high pretreatment SII level is a negative independent prognosticator of survival outcomes in mCRPC with sequential therapy using DP followed by AA or vice versa, which might guide clinicians select the best treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 36 publications
2
58
0
1
Order By: Relevance
“…No available studies were obtained from the Cochrane Library database. A total of 14 studies (11 full-text studies and 3 conference abstracts) were finally included in the present meta-analysis [ 9 , 12 , 13 , 14 – 24 ]. Figure 1 shows the study selection process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No available studies were obtained from the Cochrane Library database. A total of 14 studies (11 full-text studies and 3 conference abstracts) were finally included in the present meta-analysis [ 9 , 12 , 13 , 14 – 24 ]. Figure 1 shows the study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Poor outcomes have been recently reported in patients with high SII values based on studies of other cancers, such as respiratory system cancers and digestive system cancers [ 7 , 8 , 11 ]. There is still a debate for the use of SII in urologic cancers, although an increasing number of studies has been performed on this topic, and the sample size in the existing research is not that large [ 12 , 13 ]. Therefore, we conducted a meta-analysis to investigate the prognostic role of SII in patients with urologic cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that peripheral blood cells, including neutrophils, lymphocytes, platelets, and monocytes, can promote tumor proliferation, invasion, and metastasis 12, 13. Thus, based on this evidence, many combinations of inflammatory indices such as the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and the systemic immune-inflammation index [(platelet × neutrophil)/ lymphocyte] have been used to predict the PCA prognosis 14-16. In parallel, the nutritional status of cancer patients also has been indicated as an important parameter affecting survival outcomes, including hemoglobin, albumin levels, and other nutrition indices 17-20.…”
Section: Introductionmentioning
confidence: 99%
“…The NLR and PLR have been widely used to predict the prognosis in various cancers, [6][7][8][9][10][11] and the SII has recently been determined to be an independent prognostic factor in many kinds of cancers. [22][23][24][25][26][27][28][29] These inflammation-based indexes, however, have rarely been investigated simultaneously in HER2-positive breast cancer. To the best of our knowledge, the current study is the first to comprehensively investigate and compare the prognostic values of these inflammation-based indexes in Chinese population with HER2-positive breast cancer who received scheduled adjuvant trastuzumab.…”
Section: Discussionmentioning
confidence: 99%
“…21 The systemic immune-inflammation index (SII), which is a parameter integrates neutrophils, platelets and lymphocytes, has recently been assessed in various solid cancers: colorectal cancer, nasopharyngeal cancer, hepatocellular cancer, pancreatic cancer, gastric cancer and prostate cancer. [22][23][24][25][26][27][28][29] A recent study evaluated the prognostic significance of SII in hormone receptor (HR)-negative, HER2positive breast cancer, and showed that an increased SII independently predicted poor survival for HER2-positive breast cancer patients. 30 In this study, the median DFS rates of 15.1 and 31.5 months in high and low SII patients, respectively, indicated that the included patients were at an extremely high risk, as in the BCIRG006 trial, the 10-year DFS rate was as high as 75% in the general population.…”
Section: Introductionmentioning
confidence: 99%